Electromagnetic fields: 300Hz to 300 GHz (Geneva, 1993)
A critical review of all data relevant to the assessment of human health effects associated with exposure to electromagnetic fields in the frequency range of 300 Hz to 300 GHz. Emphasis is placed on new data that shed light on the interactions of electromagnetic fields with biological systems and on the specific biological effects and responses that result. Over 500 recent studies were rigorously assessed. Sources of exposure considered include broadcasting systems, microwave ovens, induction heating stoves, visual display units, television receivers, dielectric heaters for industrial use, radar installations, and medical devices and procedures.